The effect of stress concentrations on fatigue and fracture of 316L stainless steel micro-scale components - Wiersma, Susanne Amanda (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2004)
The aim of this work was to investigate the fatigue and fracture behaviour of microscopic specimens based on a biomedical component (the cardiovascular stent) and to modify existing theories to take account of the observed effects. A stent is a cylindrical wire mesh that is used to scaffold open stenosed arteries in order to retain a sufficient blood flow. Different 316L stainless steel microscopic specimens were designed and tested, which contained notches representing stent-like features. Typical sizes of stent wires are around 100μm, giving only about 10 grains along the width and thickness of the wires.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin